Trophic resource partitioning drives fine‐scale coexistence in cryptic bat species. Issue 24 (11th November 2020) - Novella‐Fernandez, Roberto; Ibañez, Carlos; Juste, Javier; Clare, Elizabeth L.; Doncaster, C. Patrick; Razgour, Orly
Abstract: Understanding the processes that enable species coexistence has important implications for assessing how ecological systems will respond to global change. Morphology and functional similarity increase the potential for competition, and therefore, co‐occurring morphologically similar but genetically unique species are a good model system for testing coexistence mechanisms. We used DNA metabarcoding and high‐throughput sequencing to characterize for the first time the trophic ecology of two recently described cryptic bat species with parapatric ranges, Myotis escalerai and Myotis crypticus . We collected fecal samples from allopatric and sympatric regions and from syntopic and allotopic locations within the sympatric region to describe the diets both taxonomically and functionally and compare prey consumption with prey availability. The two bat species had highly similar diets characterized by high arthropod diversity, particularly Lepidoptera, Diptera and Araneae, and a high proportion of prey that is not volant at night, which points to extensive use of gleaning. Diet overlap at the prey item level was lower in syntopic populations, supporting trophic shift under fine‐scale co‐occurrence. Furthermore, the diet of M. escalerai had a marginally lower proportion of not nocturnally volant prey in syntopic populations, suggesting that the shift in diet may be driven by a change in foraging mode. Our findings suggest that fine‐scale coexistence mechanisms can have implications for maintaining broad‐scale diversity patterns. This study highlights the importance of including both allopatric and sympatric populations and choosing meaningful spatial scales for detecting ecological patterns. We conclude that a combination of high taxonomic resolution with a functional approach helps identify patterns of niche shift. Abstract : We used DNA metabarcoding, high‐throughput sequencing, and a functional approach to test the role of trophic partitioning in enabling species coexistence across spatial scales through characterizing the trophic ecology of two cryptic bat species, Myotis escalerai and Myotis crypticus, in sympatric versus allopatric locations. Although the two species had similar diets characterized by high arthropod diversity, diet overlap at the prey‐item level was lower in locally sympatric than allopatric locations; and the functional analysis suggested that this trophic shift may be driven by a change in foraging mode from gleaning to aerial hawking. Our findings show that fine‐scale coexistence mechanisms can contribute to maintaining broad‐scale diversity patterns.